ANALISIS ATAS UU. NOMOR 13 TAHUN 2003 TENTANG PEKERJA ANAK - Subaidi; Subyanto (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2022)
Employing minors is ordering or allowing children under eighteen to work like adults in order to obtain materials for their own needs, to help their families, or to exploited by the people who employ them.In Islam, minors have a special position and have rights to be given by the people who are responsible for them. These rights include earning a living, education, preparation for the future, protection of their assets by their family or mahram. Therefore, there is no right for fathers and mothers, especially besides those twotoforce their children to work and earn a living.